An Overview of The Role of the Supreme Court in Shaping the Juvenile Justice System in India - Shyam Kishore Mishra,; Professor (Dr.) Vidya Shaktawat, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research article focuses on the topic “An overview of the role of Supreme Court in shaping the juvenile justice system in India”. The concept of juvenile justice in India has been influenced by international standards, especially the United Nations Convention on the Rights of the Child (UNCRC) 1989, but the active role of the Supreme Court has been very important in its practical implementation and strengthening. The Supreme Court through its various judgements has made it clear that a policy of rehabilitation, reform and reintegration should be adopted instead of a punitive approach towards juvenile offenders. In important cases like Shefali v. State, Pratap Singh v. State of Jharkhand, Salil Bali v. Union of India, the Court gave concrete guidelines on determination of age of juvenile, protection of rights, and due process. The Court also ensured that the provisions of the Juvenile Justice Acts, 2000 and 2015 are interpreted constitutionally in a manner that strengthens opportunities for child protection, education, and rehabilitation. This research article highlights the fact that the activism of the Supreme Court not only contributed to the interpretation and reform of the Juvenile Justice Acts but also laid the foundation of a humane justice system that provides juveniles an opportunity to lead a dignified life. Thus, the development of the Indian juvenile justice system has not been limited to legislative reforms only but it has also become more sensitive, humane and effective due to judicial interventions.
Keywords: Juvenile Justice; Supreme Court; Rehabilitation; Human Rights; Child Protection; Judicial Activism. Juvenile Delinquency; Act 2015; Correctional Homes